2010
DOI: 10.1111/j.1551-2916.2010.03743.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Properties of the Ruddlesden–Popper Series, Lan+1NinO3n+1 (n=1, 2, and 3), as Intermediate‐Temperature Solid Oxide Fuel Cells

Abstract: The Ruddlesden–Popper phases, Lan+1NinO3n+1 (n=1, 2, and 3), were synthesized by a solid‐state reaction for use as cathodes in an intermediate‐temperature (500°–700°C) solid oxide fuel cell. The samples crystallized into an orthorhombic layered perovskite structure. The overall electrical conductivity increased with the increase of n in the intermediate temperature range. Single test‐cells, which consisted of samarium‐oxide‐doped ceria (SDC; Sm0.2Ce0.8Ox) as an electrolyte, Ni–SDC cermet (Ni–SDC) as an anode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 17 publications
1
56
1
Order By: Relevance
“…An electrolytesupported single cell (LSNO-YSZ/YSZ/Ce-Pd-YSZ) based on a ∼120 μm YSZ electrolyte was fabricated to measure the electrochemical performance of the LNO-YSZ cathode. The maximum power density of the LNO nanocomposite was 0.385 W cm −2 at 700 • C. In comparison with the power density of bulk LNO, 4,19,31,32 the value of LNO here is reasonable considering that a thick YSZ electrolyte (∼120 μm) was used in this study without any buffer layer. The electrolyte is responsible for the higher ohmic resistance and consequently lower power density.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…An electrolytesupported single cell (LSNO-YSZ/YSZ/Ce-Pd-YSZ) based on a ∼120 μm YSZ electrolyte was fabricated to measure the electrochemical performance of the LNO-YSZ cathode. The maximum power density of the LNO nanocomposite was 0.385 W cm −2 at 700 • C. In comparison with the power density of bulk LNO, 4,19,31,32 the value of LNO here is reasonable considering that a thick YSZ electrolyte (∼120 μm) was used in this study without any buffer layer. The electrolyte is responsible for the higher ohmic resistance and consequently lower power density.…”
Section: Resultsmentioning
confidence: 85%
“…19,29,31 Thus, it can be concluded that the LNO nanocomposite has lower ASR with faster oxygen diffusion kinetics in the cathode than the bulk LNO. Additionally, Figure 5 shows that the cathode ASR values of LSNO4 and LSNO8 cathodes are 0.195, 0.274 cm 2 , respectively, at 700…”
Section: Resultsmentioning
confidence: 99%
“…Total conductivity in these R-P phases is known to increase with n [7,24], and it has been shown that this is maintained in porous electrode layers [9], so it is consistent that an outer L4N3 layer lowers the polarisation resistance. Current collectors are known to improve electrode performance and have been utilised with these La-Ni R-P materials before [16,17,25].…”
Section: Electrochemical Testingmentioning
confidence: 75%
“…[ 349 ] More intriguingly, they may also show an improved ORR activity than La 2 NiO 4 . [348][349][350][351] Oxygen hypo-stoichiometry, instead of hyperstoichiometry, was typically observed in these high-order Ruddlesden-Popper phases. [ 261,354 ] In a recent study, Woolley et al precisely determined the valence state of Ni in La 2 NiO 4+δ and La 4 Ni 3 O 10-δ by X-ray absorption spectroscopy of the near-edge region of the Ni K-edge at room temperature and 650 °C.…”
Section: Ruddlesden-popper-type Metal Oxidesmentioning
confidence: 97%
“…[ 348 ] The electrochemical performance of these higher order Ruddlesden-Popper phases has been investigated. [ 261,348,349,351 ] From symmetrical cell tests, the La 4 Ni 3 O 9.78 coated LSGM electrolyte pellet yielded the lowest ASR of ≈1 Ω cm 2 at 800 °C with an activation energy of E a = 1.36 eV, followed by La 3 Ni 2 O 6.95 and La 2 NiO 4.15 with E a = 1.27 and 1.24 eV, respectively. [ 348 ] The peak power densities of a cell with a La 4 Ni 3 O 10 electrode reached 10.2, 36.5, and 88.2 mW cm −2 at 500, 600, and 700 °C, respectively.…”
Section: Ruddlesden-popper-type Metal Oxidesmentioning
confidence: 98%